2016
DOI: 10.5897/ajmr2016.8156
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Escherichia coli in treated wastewater used for food production in Morogoro, Tanzania

Abstract: The aim of this study was to assess the removal efficiency of Escherichia coli at Mafisa and Mzumbe domestic wastewater treatment ponds in Morogoro, Tanzania. The study was done from October, 2013 to April, 2014. A total of 125 water samples from inlets and subsequent anaerobic, facultative and maturation ponds as well as treated wastewater were collected and analysed for E. coli. The estimated retention times of the wastewater treatment units were 19 and 22 days in Mafisa and Mzumbe ponds, respectively. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Studies have indicated that faecal coliform counts in WSPs effluent do not allow for effluent reuse for unrestricted irrigation of many crops without further treatment (Afifi, 2005). Ofred et al (2016) conducted a study in Tanzania on the performance of anaerobic, facultative and maturation ponds and observed varying concentrations of pollutants in each pond. There are different investigations that have been conducted to improve WSPs.…”
Section: Evaluation Of Waste Stabilisation Pond Units For Treating Domestic Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that faecal coliform counts in WSPs effluent do not allow for effluent reuse for unrestricted irrigation of many crops without further treatment (Afifi, 2005). Ofred et al (2016) conducted a study in Tanzania on the performance of anaerobic, facultative and maturation ponds and observed varying concentrations of pollutants in each pond. There are different investigations that have been conducted to improve WSPs.…”
Section: Evaluation Of Waste Stabilisation Pond Units For Treating Domestic Wastewatermentioning
confidence: 99%
“…Ofred et al . (2016) conducted a study in Tanzania on the performance of anaerobic, facultative and maturation ponds and observed varying concentrations of pollutants in each pond. There are different investigations that have been conducted to improve WSPs.…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, waste stabilization ponds (WSPs) have been used for municipal wastewater treatment for several decades [1]. Effluents from various WSP systems are used for urban agricultural activities, such as vegetable gardening in Iringa [2], and vegetable and rice paddy farming in Moshi [3] and Morogoro [4]. Using WSP effluent for irrigation was observed to benefit farmers.…”
Section: Introductionmentioning
confidence: 99%